Detection of P53 Protein Changes in the Tissues of 1,2 Dimethyl Hydrazine and Zingiber Officinale Root Extract Treated Syrian Hamster Using Real-Time Polymerase Chain Reaction and Immunohistochemistry Staining - Ibrahim, Nahla (Latakia University Journal -Biological Sciences Series, 2024)
Colon cancer is the third common type of cancer in the world, that is characterized by the emergence of malignant cells in the mucous membrane and the loss of the mechanism of natural control over growth. Because of the high cost and long-term side effects of chemical and immune treatments, we aimed to highlight the possibility of using the Zingiber in the treatment of cancer. Zingiber is one of the most important medical plants and plays a protective role against this disease. Our study contained 110 individuals of Syrian hamster divided into six groups: the first group witness (10 individuals) was given food and distilled, the second group (20 individuals) was dosed daily with Zingiber (80 mg/kg) for 8 Weeks, the third group (20 individuals) was dosed daily with Zingiber (220 mg/kg) for 8 weeks, the fourth group (20 individuals) was injected with a compound 1,2 Dimethyl Hydrazine (40 mg/kg) in the abdomen at a rate of 4 times/week For 8 weeks, the fifth group (20 individuals) was dosed for a week with ginger extract (80 mg/kg) in conjunction with 1,2 Dimethyl Hydrazine (40 mg/kg) 4 times/week for 8 weeks, the sixth group (20 individuals) has been fed for a week with vegetable extract, then with Zingiber extract (220 mg/kg) in conjunction with 1,2 Dimethyl Hydrazine injection (40 mg/kg) 4 times/week for 8 weeks. At the end of the experiment, the colon tissue was obtained from the previous six groups animals, nucleic acids extraction, Real-Time Polymerase chain reaction and the immunohistochemistry staining were performed to detect the P53 protein changes. The results of our current study showed that 1,2 Dimethyl Hydrazine is capable of causing a mutation in the P53 protein. This was demonstrated by an increase in its gene expression within colon tissue, which led to neoplastic transformation. On the other hand, the aqueous extract of Zingiber roots prevented neoplastic transformation in the colon tissue of experimental animals, and this was evident through reducing the sinusoidal expression of the P53 protein and maintaining its normal level within the tissue.